Transformasi Ideologi dan Kritik Rasional terhadap Hadis Mut’ah: Studi Hermeneutis Interpretasi Sayyīd Ḥusain Al-Mūsawī - Reza, Raja Fahrul (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2022)
This study aims to explore Ḥusain Al-Mūsawī's Interpretation of the Mut'ah Hadiths in his book Lillāhi Thumma Lī Al-Tārīkh: Kashfu Al-Asrāri Wa Tabri'atu Al-A'immati Al-Athār and how the Context of Ḥusain Al-Mūsawī's Ideological Shift Affects His Interpretation of the Mut'ah Marriage Hadiths. This discussion is interesting because nikah mut'ah, which is doctrinally considered valid in the Shi'a tradition, was sharply criticized by a scholar of ahl al-Bait, who was previously part of the Shi'a scholar himself. As an insider-turned-internal critic, Al-Mūsawī displays a deep intellectual and spiritual struggle, reflecting the tension between tradition and rationality. This study uses a qualitative method with Gadamer's hermeneutic analysis knife to understand the involvement of historical context in the interpretation of texts. This study found that Ḥusain Al-Mūsawī's interpretation of the nikah mut'ah hadith underwent significant changes as a result of his ideological shift from the Shi'a school to a more rational and contextual approach. Al-Mūsawī considers that the hadiths that support mut'ah, even though they are found in the books of Shi'a mu'tabar, are no longer worthy of argument because they are full of distortions of meaning, contrary to the Qur'an, common sense, and modern social values. In addition, he also considered his historical awareness and life experiences in reading the hadith texts. The transformation of Sayyid Husain al-Musawi's thought shows how pre-understanding and historical experience can reshape the meaning of religious texts. His criticism of mut'ah and other Shi'a doctrines is not merely an emotional reaction, but an intellectual reflection rooted in moral and scientific responsibility. This study opens up space for a more critical and inclusive cross-sectarian dialogue.